2013
DOI: 10.1021/bm400762h
|View full text |Cite
|
Sign up to set email alerts
|

Heterofunctional Supports in Enzyme Immobilization: From Traditional Immobilization Protocols to Opportunities in Tuning Enzyme Properties

Abstract: 27A heterofunctional support for enzyme immobilization may be defined as that which 28 possesses several distinct functionalities on its surface able to interact with a protein. We will 29 focus on those supports in which a final covalent attachment between the enzyme and the 30 support is achieved. Heterofunctionality sometimes has been featured in very old 31 immobilization techniques, even though in many instances it has been overlooked, giving rise to 32 some misunderstandings. In this respect, glutaraldeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
341
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 449 publications
(348 citation statements)
references
References 191 publications
1
341
0
1
Order By: Relevance
“…Another example are the epoxy-activated polymer supports, such as Eupergit (Katchalski-Katzir and Kraemer 2000; Erhardt and Jordening 2007) commercialized by Rhon Haas and Sepabeads commercialized by Resindion (Barbosa et al 2013). Both are available in the form of macroporous beads.…”
Section: Commercial Productsmentioning
confidence: 99%
“…Another example are the epoxy-activated polymer supports, such as Eupergit (Katchalski-Katzir and Kraemer 2000; Erhardt and Jordening 2007) commercialized by Rhon Haas and Sepabeads commercialized by Resindion (Barbosa et al 2013). Both are available in the form of macroporous beads.…”
Section: Commercial Productsmentioning
confidence: 99%
“…Meanwhile, Novozym 435 could be reused six times without significant loss of activity which indicated that the method has great potential for the preparation of salicylaldehydes. Generally, immobilization is a powerful technique to enhance the reusability and stability of enzyme [35][36][37][38]. Further study to improve the enzyme properties (mainly stability) of this lipase-catalyzed oxidation by using other immobilization strategies or even coupling immobilization and chemical modification is underway and will be reported in due course.…”
Section: Resultsmentioning
confidence: 99%
“…Now, we will present the development of tailor-made heterofunctional supports to get the specific immobilization of target proteins. Heterofunctional supports has have been recently reviewed (Barbosa et al, 2013); here we will focus on the prospects to use them to perform one step immobilization-purification.…”
Section: One-step Immobilization-purification Of Poly-lys Tagged Protmentioning
confidence: 99%
“…Heterofunctional supports are defined as those matrices that present several functionalities on its their surface, with different physical or chemical properties, able to interact with a protein (Barbosa et al, 2013, Mateo et al, 2000.…”
Section: One-step Immobilization-purification Of Poly-lys Tagged Protmentioning
confidence: 99%
See 1 more Smart Citation